2014
DOI: 10.1177/0885328214549611
|View full text |Cite
|
Sign up to set email alerts
|

Cell membrane-mimicking coating for blood-contacting polyurethanes

Abstract: The aim of the present work was to develop simple modification technique for polyurethanes (PUs) intended for use in blood-contacting implants (vascular grafts, heart prosthesis, ventricular assist devices). PU surface was modified with soybean-derived phosphatidylcholine (PC) via one-step dip coating technique. In order to evaluate blood compatibility of the obtained materials, samples were contacted with human blood under static and arterial flow-simulated conditions. The PC-modified surfaces were thoroughly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
1
15
0
1
Order By: Relevance
“…Apart from lecithin presence, the results of chemical composition analysis of nHAp-PC are comparable with results obtained for other methods for synthesis of nanoparticles of hydroxyapatite [ 20 , 23 ]. Biocompatibility of lecithin is well established in the literature [ 24 , 25 ]; thus, its presence in the synthesized nHAp-PC might be preferable for its biomedical applications.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from lecithin presence, the results of chemical composition analysis of nHAp-PC are comparable with results obtained for other methods for synthesis of nanoparticles of hydroxyapatite [ 20 , 23 ]. Biocompatibility of lecithin is well established in the literature [ 24 , 25 ]; thus, its presence in the synthesized nHAp-PC might be preferable for its biomedical applications.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This effect might be observed even when surfactants are bonded or adsorbed on the biomaterial surface. Lecithin—mixture of phosphatidylcholines, components of cellular membranes [ 24 ]—when present on the surface of any biomaterial, attracts cells to interact with the material without causing any damage to the cell membrane [ 25 ]. Aforementioned reported approaches to wet chemical precipitation allow to affect the particles morphology, but only in range from nanorods to nanopheres.…”
Section: Resultsmentioning
confidence: 99%
“…The dip‐coating technique is a conventional coating procedure that is normally used in coronary stent for drug eluting applications and to create a biocompatible surface in order to improve hemocompatibility . It is well known to be a simple and fast one‐step method with minimal requirements.…”
Section: Resultsmentioning
confidence: 99%
“…13 Finally, a strong decrease in the platelet adhesion was shown by microscopic images, and this once again confirmed the enhanced blood compatibility of the steam-modified mPE surface. 30,32 The number of platelets adhered on the steam-treated mPE sample was lower than the number of platelets found on the hydrochloric acid treated mPE sample. 10 This further confirmed that steam treatment is a powerful surface modification technique that produces optimistic changes in mPE and making it as a promising candidate for blood-contacting devices and implants.…”
Section: Articlementioning
confidence: 87%